An application of Artificial Neural Network solution in the apparel industry for Job distribution to subcontractors. (December 2022) - Mumcu, Yelda Karatepe; Kayar, Mahmut; Bulur, Öykü Ceren
Highlights: The importance of outsourcing and distribution of work to subcontract workshops were given. Criteria taken into account for applying TOPSIS, stages and implementation of TOPSIS method were given. In this study, the Artificial Neural Network method was used for the first time to estimate the result obtained by multi-criteria decision making methods. The results of the study showed that the ANN method can be applied in this area with a rate of 99% in a much shorter time. Abstract: In this study, the results of the work distribution made with the TOPSIS method, which is frequently used in the distribution of work to the subcontractor workshops, were estimated using the Artificial Neural Networks Method (ANN). Here, the C* values used in the work distribution with the TOPSIS method were estimated by ANN. The correlation coefficient of the data obtained from the created model was found to be 99.99895% for learning. According to the results, it has been concluded that work distribution can be made by using the ANN method without making complex mathematical calculations in the distribution of work to the contract workshops.